(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In coherence with the progressive digitalization of all areas of life, the Internet of Things (IoT) is a flourishing concept in both research and practice. The rapid growth and accomplishment of emerging and IoT (Internet of Things) based technologies have allowed for various possibilities in technological advancements for different aspects of life. The foremost objective of IoT technologies is to simplify processes in different fields, to ensure a better efficiency of systems and finally to improve life quality. Internet of things (IoT) is the new paradigm, has a great impact on different areas like industry, health, education, agriculture, farming and many others and its main functions are to make our life easier and more comfortable. This conceptual paper aims to understand the real applications of IoT in various sectors of the business. Various application areas of IoT technologies were discussed as well as the progress made in this research article. Energy, Transportation, Healthcare, Logistics and Retails sectors are selected for analysing the real application areas of IoT in Business. Also significant research efforts are made carefully to investigate the pros and cons of using the IoT technologies by using the various secondary sources. This study stress that an clearer understanding is needed of how the IoT will impact on the ways that organizations go about their business at all levels. Finally this study profoundly reveals that the IoT technology helps to understand the various key elements, operational domains, and various cases of applying these technologies in the business. And also proves that IoT in business is essential from the back end to the front end, creating smart products and campaigning for customers, etc.